Certainly Africa can FEED Africa - CGIAR Research Program on Climate Change, Agriculture and Food Security (2013)
Prof. Christopher Gordon says about the possibilities on how Africa can feed Africa The Forum for Agricultural Research in Africa (FARA) in collaboration with the Government of Ghana will convene the 6th Africa Agriculture Science Week from July 15-19 in Accra, a continental gathering of all stakeholders involved in African agriculture. Learn more: http://www.cgiar.org/calendar-events/africa-agriculture-science-week-2013/ http://www.fara-africa.org/scienceweek/